Efficacy and Safety of Glibenclamide Compared with Insulin in Gestational Diabetes Mellitus: A Systematic Review and Meta-analysis - Haifa, Alifia Fauziyyah; Qomariyanti, Khairunnisa; Sartika, Ratu Ayu Dewi; Sauriasari, Rani (UI Scholars Hub, 2025)
Gestational diabetes mellitus (GDM) is a prevalent pregnancy complication associated with an increased risk of maternal and neonatal complications compared with non-diabetic pregnancies. Pharmacological treatments, such as glibenclamide, are expected to provide optimal glycemic control and reduce these risks. However, concerns regarding its safety persist and some regulatory agencies have not approved glibenclamide for GDM treatment. This systematic review and meta-analysis aimed to synthesize the most recent evidence on the efficacy and safety of glibenclamide compared with insulin in the management of GDM, with a focus on maternal and neonatal outcomes based on the most recent RCT. The objective is to provide updated insight and strengthen the evidence based supporting the use of glibenclamide as treatment option for GDM. Relevant studies were identified from Pubmed, Scopus, and CENTRAL databases, resulting in 11 randomized controlled trials (RCTs) involving 2,019 participants. The pooled analysis found that glibenclamide significantly increases the risk of neonatal hypoglycemia [RR 1.65; 95% CI 1.23 to 2.22; p-value 0.0009] and significantly decreases the risk of neonatal respiratory distress syndrome (NRDS) [RR 0.56; 95% CI 0.33 to 0.95; p-value 0.03], compared to insulin. No significant differences were observed in other maternal and neonatal outcomes between the two treatments. In conclusion, glibenclamide demonstrated comparable efficacy and safety to insulin in the management of GDM, making it a viable treatment option alongside insulin.